Burden of pulmonary arterial hypertension in children globally, regionally, and nationally (1990–2021): results from the global burden of disease study - Deng, Lili; Xiong, Jingxuan; Xu, Jiaoli; Li, Qinhong; Cheng, Zugen (Frontiers in Pediatrics, 2025)
IntroductionPediatric pulmonary arterial hypertension (PAH) is a rare and severe disorder characterized by obstructive vascular changes that can lead to right heart failure. The clinical presentation and underlying causes of pediatric PAH differ significantly from those in adults, often involving congenital heart disease and developmental lung disorders, such as bronchopulmonary dysplasia (BPD). Despite advances in treatment, pediatric PAH remains underrecognized globally.MethodsThis study analyzed global, regional, and national trends in pediatric PAH from 1990 to 2021 using data from the Global Burden of Disease (GBD) database.ResultsThe findings indicate a stable prevalence rate globally, with a slight increase in the absolute number of cases. Significantly, reductions were observed in both mortality and disability-adjusted life years (DALYs) associated with pediatric PAH, with mortality decreasing by 57.66% and DALYs by 63.59% over the study period, indicating progress in mitigating the disease burden. Substantial regional disparities were identified, with low-income regions, particularly Low Socio-Demographic Index (SDI) areas, experiencing the highest mortality and DALY rates. In contrast, high-middle SDI regions showed the greatest reductions in disease burden. The highest prevalence and burden were observed in South Asia, the Caribbean, and parts of Sub-Saharan Africa, with China, India, and Haiti bearing the greatest national burdens.DiscussionThese findings highlight the necessity for targeted health interventions, especially in low-resource settings, to improve early diagnosis, intervention, and treatment.